(3eHGOF JShjb GdNOeGJs - (3GdVehQ(B, (3gGfj MGeOs ((3YeGfs (3OGQ hGFd ddfTQ hGdJhRjYs, 2021)
(3eGgjI JShjb GdNOeGJ, ecGfI GdJShjb aj eDSSGJ GdNOeGJ, eaghe GdJShjb, GdCQcGf GdCSGSjI dg, ecGfJg aj bWGY GdNOeGJ, Sdhc GdeTJQj ddNOeGJ, bQGQGJ GdeRjL GdJShjbj, GdNOeI GdLhgQ hGdNOeGJ GdJcejdjI, GdGHJcGQ hJWhjQ GdNOeGJ GdLOjOI, bQGQGJ hSjGSGJ GdJSYjQ ddNOeGJ, JCKjQ NUGFU GdNOeGJ Ydi JSYjQgG, GdCgOGa GdGSJQGJjLjI GdJSYjQjI hCfhGY GdeDSSGJ, bQGQGJ hSjGSGJ GdGJUGd GdJQhjLj, YedjI GdGJUGd GdJQhjLj, CgOGa GdJQhjL, LhGfH GdGNJdGaGJ aj JQhjL GdNOeGJ, GdeRjL GdJQhjLj hGdNOeGJ, bQGQGJ hSjGSGJ GdJhRjY, gjcd JhRjY GdNOeGJ hJQcjHg, GdYdGbI Hjf GdGSJQGJjLjI GdYGeI hGSJQGJjLjI GdJhRjY, GNJjGQ GdehbY, GdLeghQ hGdNOeGJ, OhQ GdYGedjf aj JShjb GdNOeGJ, OhQ GdYedGA aj JShjb GdNOeGJ, GdOdjd GdeGOj hGdNOeGJ, GdYedjGJ hGdNOeGJ(B.s
Keywords: (3GdJShjbs; (3JShjb GdNOeGJs